Tebing Tinggi as the Central of Onderafdeeling Padang and Bedagei - Edi Sumarno; Junita Setiana Ginting; Nina Karina; Atika Putri Ananda (Budapest International Research and Critics University, 2020)
Tebing Tinggi was originally an area under the control of the Padang Kingdom. This area had been inhabited since 1864, exactly a year after Jacobus Nienhuys started a tobacco planting business in Deli. As the development of plantation business carried out by Europeans, Tebing Tinggi also experienced changes. In its journey, Tebing Tinggi turned into an area surrounded by plantations. The existence of these plantations makes Tebing Tinggi in the future a role as the center of government for Onderafdeeling Padang and Begadei. What is behind the formation of Onderafdeeling Padang and Bedagei? How was the administration under colonial rule? What is the role of Tebing Tinggi as the center of Onderafdeeling Padang and Bedagei? These questions will be discussed in this paper. This paper uses archival sources and books published during the Dutch colonial administration. This paper aims to describe the history of Onderafdeeling Padang and Bedagei government.